Physical Activity and Injury Affect Peak Height Velocity in Children Aged 9-14 Years Old - Rifan Fauzi; Sri Sumartiningsih (Media Ilmu Keolahragaan Indonesia, 2023)
Abstract. Peak of Height Velocity is the peak of height growth in children, physical activity in children with low - high levels who are at risk of injury can hinder the child's growth period, but do high activity and injuries also affect Peak of Height Velocity. This research is to find out 1) the condition of Peak High Velocity Athletes of S3 Football School, Tugumuda Semarang and Children of Elementary School 04 Karangjati; 2) find out whether there is a relationship between physical activity and injury with Peak High Velocity; 3) to find out the difference between Peak High Velocity of Football Athletes and non-athletes. The research data was taken from 57 respondents consisting of 14 Football School S3 athletes, 21 Football School Tugu Muda athletes and 22 Children of Elementary School 04 Karangjati. The variables studied were physical condition and injury as the independent variables and PHV as the dependent variable. The data obtained were analyzed using multiple regression analysis and t test. The results showed that the size of the sports activity value was not followed by a change in the PHV value, as evidenced by the significance value for the PAQ variable of 0.441 0.05. The significance value of the injury variable is 0.736 0.05, which means that there is no significant relationship between injury and the PHV value. The average PHV in Football School reached 13.94 while those in non-Football School was 14.17 with a significance value of 0.070 0.05 which means that there was no difference in PHV between Football School and non-Football School. There is no difference in PHV between Football School and Non Football School, there is no relationship between physical activity and PHV, and there is no relationship between injury and PHV.Abstract in Indonesia. Peak of Height Velocity adalah puncak pertumbuhan tinggi badan pada anak, aktivitas fisik pada anak dengan tingkat rendah - tinggi yang beresiko cidera dapat menghambat masa pertumbuhan anak, namun apakah aktivitas tinggi dan cidera juga berpengaruh pada Peak of Height Velocity. Penelitian ini bertujuan untuk mengetahui 1) Kondisi Peak Height Velocity Atlet Sekolah Sepakbola S3,Tugumuda Semarang dan Anak SD 04 Karangjati; 2) Untuk Mengetahui apakah ada hubungan antara aktivitas fisik dan cidera dengan Peak High Velocity; 3) Untuk mengetahui perbedaan Peak Height Velocity dari Atlet Sepakbola dan bukan atlet. Data penelitian diambil dari 57 responden terdiri dari 14 responden atlet SSB S3, 21 atlet SSB Tugu Muda dan 22 siswa SD Karangjati. Variabel yang diteliti adalah kondisi fisik dan cidera sebagai variabel bebas dan PHV sebagai variabel terikat. Data yang diperoleh dianalisis menggunakan analisis regresi ganda dan uji t. Hasil penelitian menunjukkan bahwa besar kecilnya nilai aktivitas olahraga tidak diikuti dengan perubahan nilai PHV, terbukti dari nilai signifikansi untuk variabel PAQ sebesar 0,441 0.05. Nilai signifikansi dari variabel cedera sebesar 0,736 0,05, yang berarti bahwa tidak ada hubungan yang signifikan antara cedera dengan nilai PHV. Rata-tata PHV pada SSB mencapai 13,94 sedangkan yang non SSB sebesar 14,17 dengan nilai signifikansi 0,070 0,05 yang berarti bahwa tidak ada perbedaan PHV antara SSB dan non SSB.